O legendarium tolkieniano como paideia medieval - Barbosa, Jardiel Roberto da Silva (2020)
The Tolkienian narratives are an important literary material that translate a movement of resurgence of myth in the 20th century. Throughout the Legendarium, Tolkien is intentionally working with the objective of creating a mythology for England that translates an image of the human being that is consistent with the Anglo-Saxon cultural formation, rescuing elements such as the rustic robustness of the Saxons, respect for the sacred, attachment to the land, cordiality, in addition to the courageous and adventurous spirit. In view of this challenge, our hypothesis is that Tolkien is reconstructing, through literature, civilizational values of medieval Europe, a project we call medieval Paideia, that is, the author is looking for a semantic substrate for his mythological body capable of giving historical depth and at the same time philosophical and literary coherence for their narratives. A Paideia to consolidate, needs images and analogies that convey the concepts of life, transforming these concepts into semantic narratives that interpret reality from the values that society identifies as fundamental. In this sense, all Paideia presupposes civilizing human values that serve to mediate the subject to reality. Tolkien does this by rescuing models from Scandinavian mythology, the Arthurian cycle and the Christian worldview in a movement we call hybridization. These three matrixes gave the author a guiding thread for his work, which were interchanged, forming a literary synthesis with profound originality and theoretical richness. In this way, when entering the Tolkienian mythology, we can see how current the work is and at the same time rich in its literary and mythological developments, thus, throughout this work, we will approach the clipping that Tolkien makes of the medieval as an expression of a comprehensive Paideia and consistent with the whole mythical tradition of England, translating both the original narratives of this people and the Christian influence that the author translates into a literary ethos.